A NEED ANALYSIS OF APPLYING AN ENGLISH FOR SECRETARY ADMINISTRATION SKILL AND ONE YEAR PROGRAM IN INDONESIA EDUCATION INSTITUTE - Arie Wijaya Salien; Yorina An'guna Bansa (Universitas Jambi, 2019)
The Indonesian needs to improve at least in the sector of the ability to communicate in business using English. Secretary, included as one component of the administrative ranks in the business world. English for basic operational level is one of the supporting competencies in almost all of the Standards, including in the SKKNI of company service sector for office administration and secretary. This research seek “How is the current syllabus of English for profession for secretary administration program at IPI Leppindo designed?, How does the current syllabus reflect the needs of student, needs of stakeholders and the standards of SKKNI?, and What component are needed to develop syllabus in order to satisfy the needs of students, the needs of stakeholders and the standards of SKKI?”. It was a qualitative evaluation research. The data was obtained by interview, questionnaire, documentation, and observation. The minimum content of the syllabi stated in Paragraph 3 Article 12 of the Regulation of the Minister of Education and Culture Number 49 Year 2014 about National Standard of Higher Education has not been fulfilled. Furthermore, the study program has not adopted the Degree of the Minister of Labor and Transmigration Number Kep. 195/MEN/IV/2007 about The Establishment of Indonesian National Labor Competency Standards of Company Service Sector for office. The present situation analysis, strategy, and deficiency analysis were not paid attention by the institution. The results of means analysis is not matched with what has been stantdardized in the SKKNI of office administration sector for secretary administration (2007).